2018
DOI: 10.1016/j.jvs.2017.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Comparable perioperative mortality outcomes in younger patients undergoing elective open and endovascular abdominal aortic aneurysm repair

Abstract: In this study of younger patients undergoing repair of infrarenal AAA, 30-day morbidity and mortality for both open surgery and EVAR are low, and the absolute mortality difference is small. The prior published perioperative mortality and 1-year survival benefit of EVAR over open AAA repair is not observed in younger patients. Further studies of long-term durability are needed to guide decision-making for open repair vs EVAR in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Some 3061 articles were identified, of which 115 were selected and read in full. Eventually 53 studies fulfilled the inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Some 3061 articles were identified, of which 115 were selected and read in full. Eventually 53 studies fulfilled the inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…The less degree of complications leads to shorter median LOS after EVAR than after OSR, as confirmed by other studies, 19,20 both in older 21 and younger patients. 7 Consistent with these results, in many centers, the strategy of risk-benefit assessment has been replaced by an EVAR first approach, if the AAA is anatomically suitable. This is in accordance with the recent guidelines from the European Society for Vascular Surgery that recommend EVAR in most patients with suitable anatomy and reasonable life expectancy as the preferred treatment modality, being reasonable to suggest an OSR first strategy in younger, fit patients with a long life expectancy >10e15 years.…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, recent observational studies reported significantly lower postoperative complications among patients who underwent EVAR, namely lower rates of acute bowel ischemia, renal, and respiratory insufficiency 20 but also fewer rates of myocardial infarction and dysrhythmia. 7 OSR repair is a high-risk procedure which results in a severe surgical stress response. It is plausible that the lower rates of systemic complications after EVAR are due to a significantly higher incidence of systemic inflammatory response in patients who underwent OSR than in EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, EVAR is a less invasive procedure and could explain the lower morbidity, as compared to the more complex AAA-OR. In a recent study, Liang et al [36] compared perioperative and short-term outcomes in younger (<65 years) EVAR and AAA-OR patients, and found that the propensity-weighted procedural mortality rates of EVAR and AAA-OR are fairly comparable.…”
Section: Discussionmentioning
confidence: 99%